Critical thinking level among nursing students of Faculty of Medicine UKM - Mohd Esa S; Karim J; Mohamad Nurman Yaman (Penerbit Universiti Kebangsaan Malaysia, 2024)
Critical thinking plays an important role in decision-making and implementing daily tasks which includes searching, obtaining, evaluating, analysing, synthesising and conceptualising information. The aim of this study was to identify and compare the level of critical thinking among nursing students in Faculty of Medicine UKM based on systematic analysis, thinking in and out of the box domains. This was a cross-sectional study that utilised a self-administered Google Form online questionnaire on the level of critical thinking levels and domains. There were 115 nursing students in the Faculty of Medicine, UKM comprising of Year 1 (34.9%), Year 2 (26.1%), Year 3 (16.5%) and Year 4 (23.5%). The result showed that overall level of critical thinking was at intermediate level (mean=3.815, s.d=0.431) with systematic analysis domain was at intermediate level (mean=4.027, s.d=0.522), thinking in the box domain at low level (mean=2.547, s.d=0.688) and thinking out of the box domain was at intermediate level (mean=4.181, s.d=0.600). Further analysis showed that there was significant difference between students Year 2 with Year 3 and Year 3 with Year 4 in thinking out of the box domain (p=0.006). It was shown that critical thinking skills among nursing students were intermediate level.